Russia in Crisis? Prospects for the Future - Bryc, Agniszka (The Copernicus Journal of Political Studies, 2018)
The aim of the article is to outline the implications and prospects for Russia after the financial and political crisis. On one hand, Russia can continue on the current path, which has survived the impact of the global financial crisis, but which is increasingly put the country into stagnation. On the other hand, it can attempt to modernize itself – both economically and politically – in order to prepare itself for the challenges of the modern world.Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762